Domestic engineering as a factor of scientific and technological development of the Russian economy - V. N. Borisov; O. V. Pochukaevа (Модернизация, инновация, развитие)
Purpose: study of the impact of innovation and technological development of engineering industries on the effectiveness of the impact of engineering factors on the growth and development of the economy.Methods: in conducting the study, the methods and tools developed by the authors based on the scientific base and the mathematical apparatus used in economic and statistical research were used.Results: the following tasks were solved: analysis of the efficiency of the functioning of the engineering industries in terms of contribution to the formation of gross value added, import substitution and export of products; analysis of the development of engineering production and its impact on the economy of the regions of the Russian Federation. Quantitative estimates of the effectiveness of the structural and dynamic indicators of the functioning of engineering industries have been obtained. This made it possible to evaluate the effectiveness of the machinebuilding factor impact on the growth and development of the economy of the regions of the Russian Federation.Conclusions and Relevance: a special place of engineering in the structure of the economy determines the energy of its positive impact on the development of the entire industrial complex of the Russian Federation. The increase in the share of GVA, the growth of exports and import substitution indicates a positive shift in engineering towards the growth of competitiveness. Modernization of as a system of measures aimed at expanding the production base at a new technological level using the groundwork of domestic science and attracting advanced technologies is a necessary condition for involving other manufacturing industries and the entire real economy in the process of innovation and technological reequipment. It has been established that in regions with a higher level of production diversification, the influence of the mechanical-engineering factor is increasing, which contributes to an increase in the efficiency of the processing industries. The relevance of our research is due to the need to obtain quantitative estimates of the effectiveness of the functioning of the regions under the influence of a combination of factors of innovation and technological development of mechanical engineering.